ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA SMP DALAM MEMECAHKAN MASALAH MATEMATIKA MATERI BENTUK ALJABAR DITINJAU DARI GAYA KOGNITIF REFLEKTIF DAN IMPULSIF - Guvinta Rahayu; Dian Kurniati; Dhanar Dwi Hary Jatmiko; Nurcholif Diah Sri Lestari; Reza Ambarwati (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2022)
Students' critical thinking skills in learning are very important to have in the 2013 curriculum. The purpose of the study was to describe the critical thinking skills of students in SMP Negeri 7 Jember class VII J in solving mathematical problems in algebraic material, in terms of reflective and impulsive cognitive styles. This research is a descriptive study that uses a qualitative approach with 4 research subjects from class VII J consisting of 2 reflective subjects and 2 impulsive subjects. Data collection techniques used are tests and interviews. Data analysis techniques were carried out by reducing data, presenting data and drawing conclusions. Technique of data validity using triangulation method. The results of the research that have been carried out are that reflective subjects are able to meet all of the FRISCO critical thinking indicators (Focus, Reason, Inference, Situation, Clarity and Overview) in solving critical thinking test questions tend to be thorough, take a long time and the answer is correct. Impulsive subjects were only able to fulfill some of all the FRISCO critical thinking indicators (Focus, Reason, Inference, Situation, Clarity and Overview), namely focus and situation. Impulsive subjects cannot solve critical thinking questions because they do not understand how to solve problems.